Pengaruh Oxytocin Massage Terhadap Produksi ASI Pada Childbearing Family di Ruangan Melati RS TK II Robert Wolter Mongisidi - Nur Haliza Bolota; Kristine Dareda; Sri Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Oxytcin massage is a massage that can stimulate the process of breast milk production, providing a sense of comfort, relaxation and calm to help breast milk production. Childbearing family is a family that awaits birth starting from pregnancy until the birth of an early child and continues until 30 months old. The purpose of this study was to determine the effect iveness of oxytocin massage on breast milk production in childbearing families in the Melati Room of at second grade Robert Wolter Mongosidi Hospital. This research uses the Quasi Experiment method with a one group pre-test -post test design. The sample of this study amounted 17 subject using Purposive Sampling. Data collection was taken by observation sheets. Furthermore, the data that collected is analyzed using Wilcoxon's statistical test with a significant level (α) of 0.001. The results of this study showed before and after oxytocin massage most mothers experienced an increase in breast milk production. The results of the analysis tested using the Wilcoxon test obtained a value of P = 0.001 (<0.05), meaning there is an effect of oxytocin massage on breast milk production in childbearing families. The conclusion in this study the effected oxytocin massage on breast milk production in the childbearing family in the Melati Room of at second grade Robert Wolter Mongosidi Hospital.